Registered Influenza Viral Vector Based Brucella abortus Vaccine for Cattle in Kazakhstan: Age-Wise Safety and Efficacy Studies - Ryskeldinova, Sholpan; Zinina, Nadezhda; Kydyrbayev, Zhailaubay; Yespembetov, Bolat; Kozhamkulov, Yerken; Inkarbekov, Dulat; Assanzhanova, Nurika; Mailybayeva, Aigerim; Bugybayeva, Dina; Sarmykova, Makhpal; Khairullin, Berik; Tabynov, Kairat; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
A novel Influenza viral vector based Brucella abortus vaccine (Flu-BA) was introduced for use in cattle in Kazakhstan in 2019. In this study, the safety and efficacy of the vaccine was evaluated male and female cattle at different ages, and during pregnancy as a part of its registration process. Our data demonstrated that the Flu-BA vaccine was safe after prime or booster vaccination in calves (5-7 months old male and female), heifers (15-17 months old) and cows (6-7 years old) and was not abortogenic in pregnant animals. A mild, localized granuloma was observed at the Flu-BA injection site. Vaccinated animals did not show signs of influenza infection or reduced in milk production in dairy cows, and the influenza viral vector (IVV) was not recovered from nasal swabs or milk. Vaccinated animals in all age groups demonstrated increased IgG antibody responses against Brucella Omp16 and L7/L12 proteins with calves demonstrating the greatest increase in humoral responses. Following experimental challenge with B. abortus 544, vaccinates demonstrated greater protection and no signs of clinical disease, including abortion, were observed. The vaccine effectiveness against B. abortus 544 infection was 75%, 60% and 60%, respectively, in calves, heifers and adult cows. Brucella were not isolated from calves of vaccinated cattle that were experimentally challenged during pregnancy. Our data suggests that the Flu-BA vaccine is safe and efficacious in cattle, including pregnant animals; and can therefore be administered to cattle of any age.